The Effect of Leverage, Efficiency, and Liquidity on Profit Growth in Sharia Insurance Companies: A Case Study of PT Sinarmas Multiartha (2016-2023) - Ramadhan, Andika Dian; Iryana, Wahyu; Nurmalia, Gustika (Institute of Computer Science (IOCS), 2025)
This study aims to examine the effect of leverage, efficiency and liquidity on the profit growth of the sharia insurance company PT Sinarmas Multiartha for the period 2016-2023. The population in this study is the profit growth of the sharia insurance company PT Sinarmas Multiartha for the period 2016-2023. The analysis method used is the multiple linear regression analysis method carried out with the help of Eviews 10. This study uses annual data for the period 2016-2023 for each research variable. The results of this study indicate that leverage has a positive and significant effect on the profit growth of the sharia insurance company PT Sinarmas Multiartha for the period 2016-2023. Leverage has a positive and significant effect on the Profit Growth of the sharia insurance company PT Sinarmas Multiartha for the period 2016-2023. Liquidity has a positive and significant effect on the profit growth of the sharia insurance company PT Sinarmas Multiartha for the period 2016-2023. Leverage ratio, efficiency and liquidity together have a significant effect on the Profit Growth of the sharia insurance company PT Sinarmas Multiartha for the period 2016-2023